Hubungan Asupan Makronutrien dan Uang Saku dengan Status Gizi Anak Sekolah Dasar - Amilia Yuni Damayanti; Andi Dewi Santaliani; Fathimah Fathimah; Hafidhotun Nabawiyah (Poltekkes Kemenkes Mataram, 2020)
Background : Macronutrient intake can influence the concentration and intelligence of children who receive and absorb knowledge in school. Healthy foods contribute to elementary school, during school time they have the chance to consume food sold on the streets in their school. This study aimed to analyze the correlation between the intake of protein, fat, carbohydrate and pocket money on the elementary school children nutritional status. Research Methods : The study design was cross-sectional. The sample used in this study was 86 respondents selected using stratified random sampling. The data that have been collected then analyzed using a statistical gamma test. Reserch Result : The result of the study shows p=>0.05, it meant that there were no correlation between protein intake, fat intake and carbohydrate intake on nutritional status (p-value 0.281, 0.695, and 0.741). The result of pocket money on nutritional status showed that p=<0.05, which meant there was a correlation (p-value 0.002). In conclusion this study there was a correlation between pocket money on the nutritional status of elementary school children (p=0.002). So recommended that students always pay attention to the nutritional intake of food that consumed to observe the state of nutrition status